The Oxford handbook of epistemology - Moser, Paul K., 1957- (Oxford handbooks., 2002)
This reference work discusses one of the core topics of philosophy - the theory of knowledge. Connecting to virtually every other subfield, epistemology is central to mainstream philosophy. This book explains the ideas and problems of the field while avoiding overly technical detail.